Identification of Potential Anti-Blood Cancer Compounds from Centella asiatica via In Silico Approaches: Molecular Docking, ADMET Prediction, and Drug-Likeness Evaluation: Identification of Potential Anti-Blood Cancer Compounds from Centella asiatica via In Silico Approaches: Molecular Docking, ADMET Prediction, and Drug-Likeness Evaluation - Syarifah Nazila Fitriani Al-Hasany; Nily Sua’ida; Rizki Rahmadi Pratama; Halimah Halimah; Nor Syipa Hayati; Muhammad Fauzi (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2026)
Blood cancer is a hematological malignancy characterized by abnormal proliferation of blood cells due to genetic mutations. Conventional therapies such as chemotherapy and radiotherapy often cause significant side effects, highlighting the need for safer alternatives. Natural products, including Centella asiatica, have been widely explored as potential anticancer agents. This study aimed to evaluate the binding affinity, pharmacokinetic properties, and drug-likeness of bioactive compounds from Centella asiatica using an in silico approach. Molecular docking was performed using AutoDock 1.5.6 to determine binding free energy (ΔG), followed by ADMET prediction and Lipinski’s Rule of Five evaluation. The results showed that quercetin, centellin, labiatenic acid, kaempferol, and asiatic acid exhibited binding affinities of -6.51, -4.92, -5.07, -6.16, and -6.97 kcal/mol, respectively, with asiatic acid demonstrating the strongest interaction. ADMET analysis indicated generally favorable absorption and low toxicity profiles, although variability in permeability and metabolic interactions was observed. Drug-likeness evaluation revealed that most compounds met key Lipinski parameters, with minor deviations related to lipophilicity and molecular weight. In conclusion, Centella asiatica contains promising bioactive compounds with potential anti-blood cancer activity supported by favorable pharmacokinetic and drug-likeness profiles. Further in vitro and in vivo studies are required to validate these findings.